2008
DOI: 10.1111/j.1551-2916.2008.02259.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoelectric Laminate Composites: An Overview

Abstract: Since the turn of the millennium, giant magnetoelectric (ME) effects have been found in laminated composites of piezoelectric and magnetostrictive layers. Compared with ME single phase and two-phase particulate composites, laminated composites have much higher ME coefficients and are also readily fabricated. Here, we will overview the brief history of ME laminates, discussing some of the important advancements in material couples, laminate configurations, and operational modes that have allowed for dramatic en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
236
0
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 408 publications
(241 citation statements)
references
References 53 publications
1
236
0
4
Order By: Relevance
“…7 Different combinations of relative directions of the magnetization and polarization of various piezoelectric ͓for example, Pb͑Zr, Ti͒O 3 ͑PZT͔͒ and magnetostrictive phases ͑for example, metglas͒ have been attempted so far. [8][9][10] For example, the push-pull mode is a combination that consists of a structure with a longitudinally magnetized magnetic layer and a symmetrically poled piezoelectric layer about its central nodal point in reverse directions along the longitudinal axis. It has been found that three layer metglas-PZT-metglas structures offer the highest ME voltage coefficient and magnetic field sensitivity.…”
mentioning
confidence: 99%
“…7 Different combinations of relative directions of the magnetization and polarization of various piezoelectric ͓for example, Pb͑Zr, Ti͒O 3 ͑PZT͔͒ and magnetostrictive phases ͑for example, metglas͒ have been attempted so far. [8][9][10] For example, the push-pull mode is a combination that consists of a structure with a longitudinally magnetized magnetic layer and a symmetrically poled piezoelectric layer about its central nodal point in reverse directions along the longitudinal axis. It has been found that three layer metglas-PZT-metglas structures offer the highest ME voltage coefficient and magnetic field sensitivity.…”
mentioning
confidence: 99%
“…Combinations of various magnetic materials ͑for example, metglas͒ and piezoelectric phases ͑for example, Pb͑Zr,Ti͒O 3 or PZT͒, and of various relative orientations of magnetization and polarization have been studied to date. 6,7 These promising recent developments have set the ground for further investigations on structures with different magnetic and electric materials that might be useful for 1͒ practical electric-field-controlled microwave device applications and 2͒ portable and cheap, highly sensitive ME sensor applications.…”
mentioning
confidence: 99%
“…These configurations can result in longitudinal orientations for both the magnetization ͑M͒ and polarization ͑P͒, which are expected to offer a better ME coupling between layers. 7 Further, the bimorph configuration should result in a higher effective interface-driven strain because for this structure, the metglas volume in contact with PZT is a͒ Electronic mail: jaydip@vt.edu. higher than that of the unimorph configuration.…”
mentioning
confidence: 99%
“…[1][2][3][4] The ME effect in laminate composites is known to be much higher than in single phase and particulate composites, due to a combination of the magnetostrictive and piezoelectric effects of the individual layers. [5][6][7] Application of magnetic field to the laminates produces an elastic strain in the magnetostrictive phase that is stress coupled to that of the piezoelectric one, resulting in an induced voltage. Significantly higher values of the ME voltage coefficient (a ME ) have been reported in tri-layer Metglas/piezo-fibers/Metglas structures with a multi-push-pull configuration that is longitudinally and poled longitudinally magnetized (L-L).…”
mentioning
confidence: 99%